Decreased ATP, ADP and Serotonin in Young Platelets of Fawn-Hooded Rats with Storage Pool Disease - Tschopp, Th B.; Weiss, H. J (Thrombosis and Haemostasis, 1974)
The bleeding diathesis and abnormalities of platelet aggregation in the Fawn-Hooded (FH) rat, as in human patients with storage pool disease, have been attributed to decreased amounts of adenine nucleotides that are ordinarily stored with serotonin in the platelet dense granules. This study was undertaken in order to establish whether the platelet defect of the FH rat was present in young platelets, newly emerged from the bone marrow, or whether the platelets acquired this abnormality (possibly by a premature release reaction) during their circulation in the blood. FH and Wistar rats were made thrombocytopenic with one injection of anti-platelet serum (APS) and platelets were harvested during the recovery phase. The ATP content of “young” FH platelets harvested two days after injection of APS, was higher than that of platelets obtained from untreated FH rats, but was still only 50% of that found in “young” Wistar platelets. In addition, the adenine nucleotide content of FH platelets did not change during treatment with aspirin. “Young” FH platelets were also deficient in serotonin and, unlike Wistar platelets, their serotonin content did not increase appreciably with the increasing platelet age. The results of the study strongly suggest that the defect in FH platelets is present in platelets newly emerged from the bone marrow and is not due to premature release of the “storage” contents during their circulation in the blood.